A Statistical Analysis of Alleged Sexual Assaults - Its Attributes and Aftermaths - Paul, Dr. Biswadeep; Haflongbar, Dr. S.; Patowary, Dr. A. J. (International Journal of Innovative Research in Medical Science, 2018)
Sex related offences against females are universal phenomena and constitute the most shocking reprehensible crime against conscience and morality and attack on human dignity and subjugation of the fairer sex. Psychiatric disturbances, venereal diseases, attempted suicides, unwanted pregnancies; lust murder and interpersonal violence constitute far flung consequences of sexual offences including sexual assault and violence. Inspite of stringent laws including POCSO, Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redressal) Act and Criminal Law Amendment Act, sex crimes, rape and child abuse are on the rise. To analyse the antecedents and aftermaths, a statistical study was carried out on 93 female victims of alleged sexual offences who had consented for medical examination and study, on being brought to the Department. of Forensic Medicine, GMCH. Our study revealed that most of the victims were between 15 to18 years of age group with 30.11% of cases, 58.06% cases were Hindus, from urban areas with 52.69% cases, 48.39% were students, from lower socio-economic background with 73.12% cases and 79.57% were unmarried. Most of the sexual assaults occurred in the Month of September and 36.56% of the offenders were neighbours. A total of 60.22% cases had hymenal tears and 5.38% cases showed presence of spermatozoa in microscopic examination of vaginal, oral and anal smears. Comprehensive analysis of precipitating factors and evaluation of social, economic and psychological factors along with suggestion and remedial measures is the need of the hour for the benefit of the society in general and individuals in particular.